Ectopic over-expression of the maize beta-glucosidase Zm-p60.1 perturbs cytokinin homeostasis in transgenic tobacco - Kiran, Nagavalli S; Polanská, Lenka; Dopitová, Radka; Mazura, Pavel; Válková, Martina; Šmeral, Miloslav; Zouhar, Jan; Malbeck, Jiří; Dobrev, Petre I; Macháčková, Ivana; Brzobohatý, Břetislav (Journal of Experimental Botany, 2006)
The activity of the phytohormone cytokinin depends on a complex interplay of factors such as its metabolism, transport, stability, and cellular/tissue localization. O-glucosides of zeatin-type cytokinins are postulated to be storage and/or transport forms, and are readily deglucosylated. Transgenic tobacco (Nicotiana tabacum L. cv. Petit Havana SR1) plants were constructed over-expressing Zm-p60.1, a maize beta-glucosidase capable of releasing active cytokinins from O- and N3-glucosides, to analyse its potential to perturb zeatin metabolism in planta. Zm-p60.1 in chloroplasts isolated from transgenic leaves has an apparent K(m) more than 10-fold lower than the purified enzyme in vitro. Adult transgenic plants grown in the absence of exogenous zeatin were morphologically indistinguishable from the wild type although differences in phytohormone levels were observed. When grown on medium containing zeatin, inhibition of root elongation was apparent in all seedlings 14 d after sowing (DAS). Between 14 and 21 DAS, the transgenic seedlings accumulated fresh weight leading later (28-32 DAS) to ectopic growths at the base of the hypocotyl. The development of ectopic structures correlated with the presence of the enzyme as demonstrated by histochemical staining. Cytokinin quantification showed that transgenic seedlings grown on medium containing zeatin accumulate active metabolites like zeatin riboside and zeatin riboside phosphate and this might lead to the observed changes. The presence of the enzyme around the base of the hypocotyl and later, in the ectopic structures themselves, suggests that the development of these structures is due to the perturbance in zeatin metabolism caused by the ectopic presence of Zm-p60.1.
Keywords: homeostáza; Culture Media; Kinetics; Abscisic Acid; kultivační média; kukuřice setá; beta-Glucosidase; Homeostasis; kyseliny indoloctové; Cytokinins; Zea mays; cytokininy; kinetika; Plants, Genetically Modified; Nicotiana; Zeatin; Indoleacetic Acids; Financing, Organized; geneticky modifikované rostliny; beta-glukosidasa; financování organizované; zeatin; tabák; kyselina abscisová